Rumorwave: Eksplorasi Suara Manusia sebagai Representasi Ketegangan Sosial - Indriani, Dini; Apriani, Arni; Setiaji, Deden (CV. ITTC INDONESIA, 2025)
The work of Rumorwave explores the potential of the human voice as the main ingredient for the creation of contemporary music without the use of traditional instruments. By utilizing whispers, hiss, muttering, and conversation pieces, this work captures the social dynamics of gossip practices that often occur in everyday life. This research aims to explore how sound works in forming an emotional, reflective, and socially meaningful listening experience. Through an explorative-experimental approach, the creation of works is carried out through the stages of sound collection, vocal manipulation, thematic structure, and sound space packaging. The result is a musical work that is not oriented to conventional forms, but to the honesty of expression and openness of interpretation. This work is also a form of catharsis and criticism of incomplete communication patterns in modern life.